Greengo dictionary: uma análise sobre a perspectiva da análise do discurso digital e breves contribuições para os estudos em linguística popular - Sanches, Lauren de Arruda (Universidade Federal de São Carlos, 2022)
This paper analyzes the discursive functioning of the Greengo Dictionary profile on the social network Instagram. Moreover, it aims to demonstrate which elements constitute the so-called techno-discourses contained in the profile. This study seeks to understand and verify how the digital ecological discursive composition of the profile occurs through an analysis of its Instagram page. In addition, the sample we made to explain such discursive functioning also identifies the coexistence of other functions of the profile as great contributions to studies on Popular Linguistics. That being said, it is important to highlight that the way information is displayed and the elements that constitutes Greengo Dictionary make it not only a source of collaborative digital lexicon, but also an interface of linguistic interventions built by non-linguists who are inserted into a specific social network: Instagram. To do so, we will use the propositions put forward in Digital Discourse Analysis: Dictionary of Forms and Practices by Marie-Anne Paveau (2021) as theoretical and methodological bases for reflections on Popular Linguistics, which have also been proposed by Paveau (2021) and carried out in Brazil by Baronas (2021). Thus, we intend to contribute substantially to composing the knowledge about the two aforementioned theories, both of which are still being developed in Brazil.
Greengo dictionary: an analysis of the perspective of digital speech analysis and brief contributions to studies in popular linguistics
Keywords: Greengo dictionary; Análisedo discurso digital; Linguística popular; Digital discourse analysis; Popular linguistics; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA